Hydrophobic chitosan grafted silicon dioxide aerogel and preparation method thereof

By preparing chitosan-grafted silica aerogel, the problems of poor mechanical properties and uneven thermal insulation effect of existing hydrophobic silica aerogels were solved, and the preparation of high-performance hydrophobic chitosan-grafted silica aerogel with excellent mechanical and thermal insulation properties was realized.

CN121673022APending Publication Date: 2026-03-17SKYBOYS (HANGZHOU) TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511945718.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing hydrophobic silica aerogels have poor mechanical properties after modification, and their three-dimensional nano-network pore structure is uneven, which affects their thermal insulation effect.

Method used

A method for preparing chitosan-grafted silica aerogel was adopted. By controlling the mixing ratio of tetraethyl orthosilicate and chitosan, the hydrolysis and condensation reaction conditions, and the hydrophobic modification treatment, a hydrophobic chitosan-grafted silica aerogel with excellent mechanical properties and thermal insulation effect was formed.

Benefits of technology

The prepared hydrophobic chitosan-grafted silica aerogel has a good three-dimensional network structure, excellent mechanical properties and thermal insulation properties, and is suitable for the preservation and modification of porous structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of silicon dioxide aerogel, and particularly discloses hydrophobic chitosan grafted silicon dioxide aerogel and a preparation method thereof. The preparation method comprises the following steps: mixing tetraethoxysilane, deionized water and N, N-dimethylformamide to prepare a silicon solution A; mixing glacial acetic acid, deionized water and chitosan with the molecular weight of 1-100 thousand Da to prepare a chitosan solution B; mixing the silicon solution A and the chitosan solution B to prepare a mixed solution C, wherein the mass ratio of chitosan to tetraethoxysilane is 1: (90-110); adjusting the pH value of the mixed solution C to 2-4, and hydrolyzing at 40-50 DEG C for 75-120 minutes to obtain sol D; adjusting the pH value of the sol D to 7-8, and carrying out condensation polymerization for 20-60 minutes to obtain gel E; sequentially carrying out aging treatment, modification treatment and freeze drying to obtain the hydrophobic chitosan grafted silicon dioxide aerogel. The hydrophobic chitosan grafted silicon dioxide aerogel prepared by the preparation method disclosed by the invention has a relatively good three-dimensional nano network pore structure, mechanical property, hydrophobic property and heat-insulating property, and is beneficial to batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of silica aerogel technology, and more specifically, to a hydrophobic chitosan-grafted silica aerogel and its preparation method. Background Technology

[0002] Silica aerogel is a lightweight material with a three-dimensional nanoporous structure. It has high specific surface area and porosity, low thermal conductivity and other characteristics. It is currently widely used in energy conservation and environmental protection, energy construction, aerospace, biomedicine and petrochemical fields.

[0003] In existing processes, hydrophobic silica aerogels are prepared by introducing surfactants into the silicon precursor solution. However, the modified silica aerogels have a rigid framework structure and poor mechanical properties, which can easily affect their applications.

[0004] Building upon this, existing processes employ blending flexible, viscoelastic polymers with hydrophobic silica aerogels to enhance the mechanical properties of the resulting silica composite aerogels. However, since silica aerogels are inorganic materials, their structure and properties differ significantly from those of polymers, which can easily lead to uneven three-dimensional nano-network pore structures in the prepared silica composite aerogels, thus affecting their thermal insulation performance.

[0005] Therefore, a hydrophobic silica aerogel that possesses both superior mechanical properties and thermal insulation effects has a broader application prospect. Summary of the Invention

[0006] To address the issue that hydrophobic silica aerogels cannot simultaneously possess both superior mechanical properties and thermal insulation effects, this application provides a hydrophobic chitosan-grafted silica aerogel and its preparation method.

[0007] Firstly, this application provides the following technical solution: A method for preparing a hydrophobic chitosan-grafted silica aerogel includes the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide thoroughly at room temperature to obtain silicon solution A; Glacial acetic acid, deionized water and chitosan are thoroughly mixed at a temperature of 50-55℃ to obtain chitosan solution B. Step 2: Thoroughly mix silicon solution A and chitosan solution B to obtain mixture C; Step 3: Add acetic acid solution to mixture C to adjust the pH to 2-4, and then hydrolyze the mixture at 40-50℃ for 75-120 min to obtain sol D; Step 4: Add ammonia to sol D to adjust the pH to 7-8 and carry out the polycondensation reaction for 20-60 minutes to obtain gel E; Step 5: Place gel E in anhydrous ethanol for aging treatment to obtain chitosan-grafted silica wet gel F; Step 6: Immerse the chitosan-grafted silica wet gel F in a hydrophobic modification solution prepared by mixing hydrocarbon chlorosilane and n-hexane for modification treatment. After removal, wash with n-hexane to obtain hydrophobic chitosan-grafted silica wet gel G. Step 7: Freeze-dry the hydrophobic chitosan-grafted silica wet gel G to obtain hydrophobic chitosan-grafted silica aerogel. The molecular weight of the chitosan in step one is 1-100,000 Da; In step three, the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:(90-110).

[0008] In step one of this application, the solubility of tetraethyl orthosilicate (TEOS) is improved by using N,N-dimethylformamide (DMF) and deionized water, reducing the possibility of premature aggregation and making the resulting silicon solution A uniform in texture, thus providing a uniform silicon precursor environment for the subsequent hydrolysis reaction.

[0009] The molecular weight of the chitosan used in this application is controlled within the range of 1-100,000 Da. The combination of glacial acetic acid and deionized water at a temperature of 50-55°C facilitates the successful dissolution of chitosan under acidic conditions, thereby allowing its molecular chains to fully extend and preventing degradation of the chitosan molecular weight, thus providing amino and hydroxyl groups for subsequent grafting reactions.

[0010] In step two, the silicon solution A and the chitosan solution B are thoroughly mixed. During this process, the mass ratio of chitosan to tetraethyl orthosilicate is limited to ensure that the concentration of chitosan and tetraethyl orthosilicate in the mixture C is moderate and the texture is uniform, which is conducive to the subsequent hydrolysis and polycondensation reactions.

[0011] In step three, a system environment with a pH of 2-4 allows chitosan molecules to retain their active groups, and hydrolysis at 40-50℃ for 75-120 minutes ensures the complete hydrolysis of tetraethyl orthosilicate, gradually generating silanol groups (-Si-OH). Because the hydrolysis reaction is carried out in a constant-temperature water bath at 40-50℃, the possibility of excessive aggregation of silanol groups due to excessively high temperatures and a rapid hydrolysis rate is reduced, thus maintaining the uniform texture of sol D.

[0012] In step four, a condensation reaction occurs between the silanol groups in an environment with a pH of 7-8. Simultaneously, the amino and hydroxyl groups on chitosan undergo covalent condensation with the silanol groups, forming -Si-OC or -Si-N bonds, thus grafting chitosan onto silica. The condensation reaction time is controlled at 20-60 minutes, allowing for precise control of the condensation degree. This results in a three-dimensional network structure in gel E, forming a gel framework, and also reduces the possibility of excessive condensation leading to pore collapse or an overly dense structure.

[0013] In step five, gel E is treated with anhydrous ethanol. On the one hand, the anhydrous ethanol replaces the DMF and deionized water inside gel E. On the other hand, the hydroxyl groups in the anhydrous ethanol undergo secondary condensation with the silanol groups on the surface of the gel skeleton, which further improves the mechanical properties of the resulting chitosan-grafted silica wet gel F.

[0014] The hydrophobic modification solution in step six is ​​prepared by mixing hydrocarbon chlorosilanes and n-hexane. Immersion in this solution aims to graft hydrocarbon groups onto the chitosan-grafted silica wet gel F, thereby giving the hydrophobic chitosan-grafted silica wet gel G a better hydrophobic effect. Following this, washing with n-hexane removes unreacted hydrocarbon chlorosilanes and byproducts, facilitating subsequent processing.

[0015] In step seven, freeze drying is used to remove the residual solvent in the hydrophobic chitosan-grafted silica wet gel G while preserving the porous network structure of the hydrophobic chitosan-grafted silica aerogel to the greatest extent, thus maintaining its high porosity and low density, thereby giving the hydrophobic chitosan-grafted silica aerogel a good thermal insulation effect.

[0016] Furthermore, in step three, the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:(95-105).

[0017] The mass ratio of chitosan to tetraethyl orthosilicate used in this application is 1:(90-110), preferably 1:(95-105). When the above ratio is used, the mechanical properties of the final hydrophobic chitosan-grafted silica aerogel can be improved, while the silica pores are less likely to be blocked or the integrity of the silica porous structure is reduced, so that the silica aerogel also has a good thermal insulation effect.

[0018] Furthermore, in step one, the mass ratio of tetraethyl orthosilicate, deionized water and dimethylformamide is 1:(2-3):(0.25-0.45).

[0019] Preferably, in step one, the mass ratio of tetraethyl orthosilicate, deionized water and dimethylformamide is 1:(2-2.5):(0.3-0.4).

[0020] By adopting the above technical solution, it is beneficial to control the concentration of silicon solution A in step one, which in turn helps to maintain a good degree of uniformity in the mixture C when silicon solution A and chitosan solution B are fully mixed in step two.

[0021] Furthermore, in step one, the mass ratio of glacial acetic acid, deionized water and chitosan is 1: (35-55): (0.8-1.2).

[0022] Preferably, in step one, the mass ratio of glacial acetic acid, deionized water and chitosan is 1:(40-50):(1-1.2).

[0023] By adopting the above technical solution, the concentration of chitosan in chitosan solution B can be better controlled.

[0024] Furthermore, the molecular weight of chitosan in step one is 40,000-70,000 Da.

[0025] By employing the above technical solution, chitosan can be fully dissolved and its molecular chains can be fully extended, allowing for sufficient grafting with tetraethyl orthosilicate. This ensures that the final aerogel maintains excellent mechanical and thermal insulation properties. If the molecular weight of chitosan is too low, there will be fewer grafting sites, affecting the grafting effect and ultimately impacting the mechanical properties of the aerogel. Conversely, if the molecular weight of chitosan is too high, the chitosan molecular chains will not be fully extended, leading to aggregation and ultimately affecting the porous structure of the aerogel, resulting in a decrease in its thermal insulation performance.

[0026] Furthermore, in step five, during the aging process, the mass-to-volume ratio of wet gel E to anhydrous ethanol is 1:(50-100) g / ml, the aging temperature is 45-70℃, and the treatment time is 9-15 h.

[0027] Preferably, during the aging process, the mass-to-volume ratio of wet gel E to anhydrous ethanol is 1:(60-80)g / ml, the treatment temperature is 55-60℃, and the treatment time is 11-13 h.

[0028] Under the premise of reasonable cost control, the above technical solution can help to reasonably control the degree of aging treatment of wet gel E, so that the gel skeleton can fully condense and the channels in it are less likely to collapse or the entire gel skeleton will break. This improves the toughness and mechanical strength of the gel skeleton, and is also beneficial to subsequent hydrophobic treatment, so that the final aerogel has both good hydrophobicity and mechanical properties.

[0029] Further, in step six, the volume ratio of hydrocarbon chlorosilane to n-hexane is 1: (8-12); in the modification treatment, the mass-to-volume ratio of wet gel E to hydrophobic modification liquid is 1: (15-30) g / ml, and the modification treatment time is 10-15 h; The alkyl chlorosilane is one or more of the following: trimethylchlorosilane, dichlorodimethylsilane, monomethyltrichlorosilane, triethylchlorosilane, ethyltrichlorosilane, propyltrichlorosilane, tert-butyltrichlorosilane, tert-butyldimethylchlorosilane, isobutyltrichlorosilane, hexyltrichlorosilane, cyclohexyltrichlorosilane, n-octyltrichlorosilane, and phenyldimethylchlorosilane.

[0030] Preferably, the hydrocarbon chlorosilane is one or a mixture of trimethylchlorosilane, triethylchlorosilane, and phenyldimethylchlorosilane. Preferably, the volume ratio of the hydrocarbon chlorosilane to n-hexane is 1: (9-10), the mass-volume ratio of wet gel F to hydrophobic modification liquid is 1: (20-25) g / ml, and the modification treatment time is 12-14 h.

[0031] By adopting the above technical solution, the selection of hydrocarbon chlorosilanes is limited, and the ratio with n-hexane is limited within a specific range. Under the premise of sufficient hydrophobic modification liquid, the modification treatment time is limited, so that chitosan-grafted silica wet gel F is fully grafted, and the modified chitosan-grafted silica wet gel G has excellent hydrophobicity.

[0032] Furthermore, in step seven, freeze drying includes a pre-freezing treatment followed by a low-temperature drying treatment; the pre-freezing treatment time is 6 to 12 hours, and the pre-freezing treatment temperature is -15°C to -30°C; the low-temperature drying treatment time is 12 to 36 hours, and the low-temperature drying treatment temperature is -50°C to -80°C.

[0033] Furthermore, the pre-freezing treatment time is 8 to 10 hours, and the pre-freezing treatment temperature is -20℃ to -25℃; the low-temperature drying treatment time is 20 to 30 hours, and the low-temperature drying treatment temperature is -60℃ to -70℃.

[0034] By adopting the above technical solution, it is beneficial to remove the residual solvent in the hydrophobic chitosan-grafted silica wet gel G, and to make the obtained hydrophobic chitosan-grafted silica aerogel have the characteristics of three-dimensional network structure, high porosity and low density.

[0035] This application provides reasonable limits on the time and temperature of freezing treatment and the temperature and time of low-temperature drying treatment, which is beneficial for the mass production of hydrophobic chitosan-grafted silica aerogels and helps to ensure the quality of the prepared hydrophobic chitosan-grafted silica aerogels.

[0036] Furthermore, the molar concentration of the acetic acid solution in step three is 1 mol / L; and the molar concentration of the ammonia solution in step four is 5 mol / L.

[0037] By adopting the above technical solution, the pH value of the system in steps three and four can be adjusted respectively, which facilitates subsequent operations.

[0038] Secondly, this application provides the following technical solution: A hydrophobic chitosan-grafted silica aerogel was prepared using a method for preparing hydrophobic chitosan-grafted silica aerogel.

[0039] The hydrophobic chitosan-grafted silica aerogel prepared by the preparation method in this application has excellent hydrophobic properties, mechanical properties and thermal insulation properties.

[0040] In summary, this application has the following beneficial effects: 1. This application involves thoroughly mixing a silicon solution A containing tetraethyl orthosilicate and a chitosan solution B containing chitosan. Under acidic conditions, the interaction between the -OH groups in the Si-OH structure formed by the hydrolysis of tetraethyl orthosilicate and the -NH3 and -OH groups in chitosan allows chitosan to be grafted onto a silica wet gel. This not only gives the final hydrophobic chitosan-grafted silica aerogel a better three-dimensional network structure but also better mechanical properties.

[0041] 2. In this application, a hydrophobic modification solution prepared by alkylchlorosilane and n-hexane is used to modify chitosan-grafted silica wet gel F. The Cl group in the alkylchlorosilane is easy to undergo a substitution reaction with -OH and -NH3 in the chitosan-grafted silica wet gel. The alkylchlorosilane is chemically modified onto the chitosan-grafted silica wet gel F, so that the final aerogel has good hydrophobic and thermal insulation properties.

[0042] 3. This application limits parameters such as chitosan molecular weight, hydrolysis reaction, condensation reaction, aging treatment, and type of hydrocarbon chlorosilane, making the preparation process controllable and ensuring that the final aerogel has a good three-dimensional nano-network pore structure, mechanical properties, hydrophobic properties, and thermal insulation properties, which is beneficial for mass production. Attached Figure Description

[0043] Figure 1 In the figure, (a), (b), and (c) are SEM images of the aerogel samples of Example 3, Comparative Example 2, and Comparative Example 3, respectively; Figure 2 FTIR images of aerogel samples from Example 3 and Comparative Examples 1 and 3; Figure 3 The XRD patterns of the aerogel samples from Example 3 and Comparative Examples 1 and 3 are shown. Figure 4 In the image, (A) is a thermal infrared image of the upper surface of the aerogel sample in Example 3 after the lower surface of the sample was heated at a constant temperature of 40°C for 15 min. (B) is a thermal infrared image of the upper surface of the aerogel sample of Comparative Example 3 after the lower surface of the sample was heated at a constant temperature of 40℃ for 15 min. (C) is a thermal infrared image of the upper surface of the aerogel sample in Example 3 after the lower surface of the sample was heated at a constant temperature of 60°C for 15 min. (D) is a thermal infrared image of the upper surface of the aerogel sample in Comparative Example 3 after the lower surface of the sample was heated at a constant temperature of 60℃ for 15 min. Detailed Implementation Example

[0044] Example 1: A hydrophobic chitosan-grafted silica aerogel, the preparation method includes the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Glacial acetic acid, deionized water and chitosan with a molecular weight of 10,000 Da were mixed in a ratio of 1:45:1.2 and slowly stirred at 50°C to dissolve, thus obtaining chitosan solution B. Step 2: Mix and stir silica solution A and chitosan solution B at a mass ratio of tetraethyl orthosilicate to chitosan of 100:1 to obtain mixture C; Step 3: Slowly add 1 mol / L acetic acid solution to mixture C to adjust the pH to 2-4, then transfer to a 45℃ constant temperature water bath for 90 min of hydrolysis reaction to obtain sol D; Step 4: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 5: According to the mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain chitosan-grafted silica wet gel F. Step 6: Mix trimethylchlorosilane and n-hexane at a volume ratio of 1:10 to prepare a hydrophobic modification solution. Then, at a mass-volume ratio of wet gel F to hydrophobic modification solution of 1:25 g / ml, immerse the chitosan-grafted silica wet gel F in the hydrophobic modification solution at 25℃ for 12 h for modification treatment. Remove the gel and wash it three times with n-hexane to obtain hydrophobic modified chitosan-grafted silica wet gel G. Step 7: Place the hydrophobically modified chitosan-grafted silica wet gel G in a freezer at -25°C for 10 h, then remove it and dry it in a low-temperature drying oven at -70°C for 24 h to obtain hydrophobic chitosan-grafted silica aerogel.

[0045] Example 2: A hydrophobic chitosan-grafted silica aerogel, the preparation method includes the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Glacial acetic acid, deionized water and chitosan with a molecular weight of 30,000 Da were mixed in a ratio of 1:45:1.2 and slowly stirred at 50°C to dissolve, thus obtaining chitosan solution B. Step 2: Mix and stir silica solution A and chitosan solution B at a mass ratio of tetraethyl orthosilicate to chitosan of 100:1 to obtain mixture C; Step 3: Slowly add 1 mol / L acetic acid solution to mixture C to adjust the pH to 2-4, then transfer to a 45℃ constant temperature water bath for 90 min of hydrolysis reaction to obtain sol D; Step 4: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 5: According to the mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain chitosan-grafted silica wet gel F. Step 6: Mix trimethylchlorosilane and n-hexane at a volume ratio of 1:10 to prepare a hydrophobic modification solution. Then, at a mass-volume ratio of wet gel F to hydrophobic modification solution of 1:25 g / ml, immerse the chitosan-grafted silica wet gel F in the hydrophobic modification solution at 25℃ for 12 h for modification treatment. Remove the gel and wash it three times with n-hexane to obtain hydrophobic modified chitosan-grafted silica wet gel G. Step 7: Place the hydrophobically modified chitosan-grafted silica wet gel G in a freezer at -25°C for 10 h, then remove it and dry it in a low-temperature drying oven at -70°C for 24 h to obtain hydrophobic chitosan-grafted silica aerogel.

[0046] Example 3: A hydrophobic chitosan-grafted silica aerogel, the preparation method includes the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Glacial acetic acid, deionized water and chitosan with a molecular weight of 50,000 Da were mixed in a ratio of 1:45:1.2 and slowly stirred at 50°C to dissolve, thus obtaining chitosan solution B. Step 2: Mix and stir silica solution A and chitosan solution B at a mass ratio of tetraethyl orthosilicate to chitosan of 100:1 to obtain mixture C; Step 3: Slowly add 1 mol / L acetic acid solution to mixture C to adjust the pH to 2-4, then transfer to a 45℃ constant temperature water bath for 90 min of hydrolysis reaction to obtain sol D; Step 4: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 5: According to the mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain chitosan-grafted silica wet gel F. Step 6: Mix trimethylchlorosilane and n-hexane at a volume ratio of 1:10 to prepare a hydrophobic modification solution. Then, at a mass-volume ratio of wet gel F to hydrophobic modification solution of 1:25 g / ml, immerse the chitosan-grafted silica wet gel F in the hydrophobic modification solution at 25℃ for 12 h for modification treatment. Remove the gel and wash it three times with n-hexane to obtain hydrophobic modified chitosan-grafted silica wet gel G. Step 7: Place the hydrophobically modified chitosan-grafted silica wet gel G in a freezer at -25°C for 10 h, then remove it and dry it in a low-temperature drying oven at -70°C for 24 h to obtain hydrophobic chitosan-grafted silica aerogel.

[0047] Example 4: A hydrophobic chitosan-grafted silica aerogel, the preparation method includes the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Glacial acetic acid, deionized water and chitosan with a molecular weight of 100,000 Da were mixed in a ratio of 1:45:1.2 and slowly stirred at 50°C to dissolve, thus obtaining chitosan solution B. Step 2: Mix and stir silica solution A and chitosan solution B at a mass ratio of tetraethyl orthosilicate to chitosan of 100:1 to obtain mixture C; Step 3: Slowly add 1 mol / L acetic acid solution to mixture C to adjust the pH to 2-4, then transfer to a 45℃ constant temperature water bath for 90 min of hydrolysis reaction to obtain sol D; Step 4: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 5: According to the mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain chitosan-grafted silica wet gel F. Step 6: Mix trimethylchlorosilane and n-hexane at a volume ratio of 1:10 to prepare a hydrophobic modification solution. Then, at a mass-volume ratio of wet gel F to hydrophobic modification solution of 1:25 g / ml, immerse the chitosan-grafted silica wet gel F in the hydrophobic modification solution at 25℃ for 12 h for modification treatment. Remove the gel and wash it three times with n-hexane to obtain hydrophobic modified chitosan-grafted silica wet gel G. Step 7: Place the hydrophobically modified chitosan-grafted silica wet gel G in a freezer at -25°C for 10 h, then remove it and dry it in a low-temperature drying oven at -70°C for 24 h to obtain hydrophobic chitosan-grafted silica aerogel.

[0048] Example 5: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of tetraethyl orthosilicate, deionized water and N,N-dimethylformamide is 1: 2.5: 0.25.

[0049] Example 6: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of tetraethyl orthosilicate, deionized water and N,N-dimethylformamide is 1:3:0.45.

[0050] Example 7: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of acetic acid, deionized water and chitosan is 1:35:0.8.

[0051] Example 8: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of acetic acid, deionized water and chitosan is 1:55:1.2.

[0052] Example 9: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of acetic acid, deionized water and chitosan is 1:40:1.

[0053] Example 10: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step one, the mass ratio of acetic acid, deionized water and chitosan is 1:50:1.2.

[0054] Example 11: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the chitosan used in step one has a molecular weight of 40,000.

[0055] Example 12: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the chitosan used in step one has a molecular weight of 70,000.

[0056] Example 13: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:90.

[0057] Example 14: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:95.

[0058] Example 15: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:105.

[0059] Example 16: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the mass ratio of chitosan to tetraethyl orthosilicate in mixture C is 1:110.

[0060] Example 17: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step six, the volume ratio of trimethylchlorosilane to n-hexane in the hydrophobic modification solution is 1:8.

[0061] Example 18: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step six, the volume ratio of trimethylchlorosilane to n-hexane in the hydrophobic modification solution is 1:12.

[0062] Example 19: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step six, the mass-to-volume ratio of chitosan-grafted silica wet gel E to hydrophobic modification liquid is 1:15 g / ml.

[0063] Example 20: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that: in step six, the mass-to-volume ratio of chitosan-grafted silica wet gel E to hydrophobic modification liquid is 1:25 g / ml.

[0064] Example 21: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the hydrophobic modification time in step six is ​​10 hours.

[0065] Example 22: A hydrophobic chitosan-grafted silica aerogel, which differs from Example 3 in that the hydrophobic modification time in step six is ​​15 hours.

[0066] Comparative Example Comparative Example 1: A chitosan-grafted silica aerogel, prepared by the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Glacial acetic acid, deionized water and chitosan with a molecular weight of 50,000 Da were mixed in a ratio of 1:45:1.2 and slowly stirred at 50°C to dissolve, thus obtaining chitosan solution B. Step 2: Mix and stir silica solution A and chitosan solution B at a mass ratio of tetraethyl orthosilicate to chitosan of 100:1 to obtain mixture C; Step 3: Slowly add 1 mol / L acetic acid solution to mixture C to adjust the pH to 2-4, then transfer it to a 45℃ constant temperature water bath for 90 min for hydrolysis reaction to obtain sol D; Step 4: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 5: Place wet gel D in anhydrous ethanol at 60℃ for 12 h of aging treatment at a mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml to obtain chitosan-grafted silica wet gel F. Step 6: First, pre-freeze the chitosan-grafted silica wet gel F in a freezer at -25°C for 10 h, then remove it and dry it in a low-temperature drying oven at -70°C for 24 h to obtain chitosan-grafted silica aerogel.

[0067] Comparative Example 2: A hydrophobic chitosan-grafted silica aerogel, prepared by the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A.

[0068] Step 2: Add 1 mol / L acetic acid solution to silicon solution A to adjust the pH to 2-4, and then transfer it to a 45℃ constant temperature water bath for 90 min for hydrolysis reaction to obtain sol D.

[0069] Step 3: Add 5 mol / L ammonia to sol F to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E.

[0070] Step 4: With a mass-to-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain silica wet gel F.

[0071] Step 5: Prepare a hydrophobic modification solution by mixing trimethylchlorosilane and n-hexane at a volume ratio of 1:10. Then, immerse the silica wet gel F in the hydrophobic modification solution at a mass-to-volume ratio of 1:25 g / ml for 12 h. Remove the gel and wash it three times with n-hexane to obtain the hydrophobic silica wet gel G.

[0072] Step 6: First, place the hydrophobic silica wet gel G in a freezer at -25℃ for 10 h, then remove it and dry it in a low-temperature drying oven at -70℃ for 24 h to obtain the hydrophobic silica aerogel.

[0073] Comparative Example 3: A silica aerogel, prepared by the following steps: Step 1: Mix tetraethyl orthosilicate, deionized water and N,N-dimethylformamide in a ratio of 1:2:0.35 and stir at 25°C to dissolve and obtain silicon solution A; Step 2: Add 1 mol / L acetic acid solution to silicon solution A to adjust the pH to 2-4, and then transfer it to a 45℃ constant temperature water bath for 90 min for hydrolysis reaction to obtain sol D; Step 3: Add 5 mol / L ammonia to sol D to adjust the pH to 7-8 and carry out a condensation reaction for 40 min to obtain wet gel E; Step 4: According to the mass-volume ratio of wet gel E to anhydrous ethanol of 1:70 g / ml, wet gel E is placed in anhydrous ethanol at 60℃ for 12 h for aging treatment to obtain silica wet gel F. Step 5: First, place the silica wet gel F in a freezer at -25℃ for 10 h for pre-freezing treatment, then take it out and place it in a low temperature drying oven at -70℃ for 24 h to dry it, thus obtaining silica aerogel.

[0074] Comparative Example 4: A chitosan-grafted silica aerogel, the difference from Comparative Example 1 is that the chitosan used in step one has a molecular weight of 5000 Da.

[0075] Comparative Example 5: A chitosan-grafted silica aerogel, the difference from Comparative Example 1 is that the chitosan used in step one has a molecular weight of 110,000 Da.

[0076] Comparative Example 6: A chitosan-grafted silica aerogel, which differs from Example 3 in that the chitosan used in step one has a molecular weight of 110,000 Da.

[0077] Characterization experiment The aerogel samples in the examples and comparative examples were tested using the following methods, and the data were recorded and analyzed; ① The specific surface area of ​​the aerogel was analyzed using a fully automated specific surface area and porosity analyzer (BET, Micromeritics ASAP 2460, USA); ② The volume shrinkage rate and porosity of the aerogel sample are calculated according to Equation (1) and Equation (2), respectively; (1) (2) In equation (1), V is the volume of the aerogel sample, and V1 is the volume of the freeze-dried wet gel sample; In formula (2), m1 is the mass of the aerogel sample, m2 is the mass of the aerogel sample after soaking in anhydrous ethanol for 24 h and draining, and ρ 醇 That is the density of ethanol; ③ The mechanical properties of the aerogel samples were analyzed using an electronic universal testing machine (Fuletest FL5000); ④ Measure the water contact angle of the aerogel sample using a surface tension meter (Chengde Dingsheng JY / 82C); ⑤ The thermal conductivity of the aerogel samples was measured using a thermal conductivity meter (Kyoto Electronics QTM / 500, Japan).

[0078] The volume shrinkage rate, specific surface area, porosity, mechanical properties, hydrophobic properties and thermal conductivity of the aerogel samples of Examples 1-22 and Comparative Examples 1-6 are shown in Table 1.

[0079] Table 1. Volume shrinkage, specific surface area, porosity, mechanical properties, hydrophobic properties, and thermal conductivity of aerogel samples from Examples 1-22 and Comparative Examples 1-6.

[0080] Referring to Table 1, the difference between Comparative Example 1 and Example 3 is that the hydrophobic modification treatment in step six is ​​not used. The volume shrinkage rate, specific surface area, porosity, compressive stress at 80% strain, and compressive modulus of the aerogel samples in Example 3 and Comparative Example 1 are relatively similar. However, the water contact angle of Example 3 is significantly increased, and the thermal conductivity is significantly decreased compared to Comparative Example 1. This result indicates that the hydrophobic modification treatment used in this application plays a crucial role in improving the thermal insulation performance of silica aerogels.

[0081] The difference between Comparative Example 2 and Example 3 is that chitosan solution B was not used and chitosan-related steps were omitted. Compared to Comparative Example 2, Example 3 showed a slight decrease in volume shrinkage, specific surface area, and porosity, while its compressive stress and compressive modulus at 80% strain were significantly increased. The water contact angle and thermal conductivity of both examples were similar. These results indicate that, on the one hand, the addition of chitosan increases the crosslinking density of the aerogel, promoting the formation of silica particles with a "nano-bridging" structure, thereby effectively inhibiting the drying shrinkage of the silica gel; on the other hand, the coexistence of hydrogen bonding between chitosan and siloxanes and siloxane condensation leads to a strong bond between amorphous silica and chitosan, reducing the volume shrinkage of the silica gel during drying. Therefore, chitosan grafting plays a crucial role in improving the thermal insulation and mechanical properties of aerogel samples.

[0082] The difference between Comparative Example 3 and Example 3 is that chitosan solution B is not used and the steps related to chitosan are omitted, and the hydrophobic modification treatment in step six is ​​not used.

[0083] A comparison of the volume shrinkage rate, specific surface area, and porosity data of Examples 1-4, 11-12, and Comparative Examples 4-5 reveals that the volume shrinkage rate of Examples 1-4 and 11-12 is lower than that of Comparative Example 4-5, the specific surface area of ​​Examples 1-4 and 11-12 is higher than that of Comparative Example 4-5, and the porosity of Examples 1-4 and 11-12 is higher than that of Comparative Example 4-5. The difference between Examples 1-4, 11-12, and Comparative Example 4-5 lies in the molecular weight of chitosan. Therefore, the above results indicate that changes in the molecular weight of chitosan affect the volume shrinkage rate, specific surface area, and porosity of the aerogel samples.

[0084] Further analysis of the data from Examples 1-4 and Examples 11-12 revealed that, with increasing chitosan molecular weight, the volume shrinkage rate of the aerogel samples initially decreased and then increased, while the specific surface area and porosity initially increased and then decreased, although the magnitudes of these increases and decreases were relatively small. This result indicates that a higher chitosan molecular weight is not always better for preparing aerogel samples. When the chitosan molecular weight exceeds the range specified in this application, whether too large or too small, it affects the volume shrinkage rate, specific surface area, and porosity of the aerogel samples. This also demonstrates that the chitosan molecular weight influences the three-dimensional network structure of the aerogel samples.

[0085] A comparison of the compressive stress and compressive modulus data at 80% strain between Examples 1-4, Examples 11-12, and Comparative Examples 4-5 reveals that the compressive stress and compressive modulus at 80% strain in Examples 1-4 and 11-12 are higher than those in Comparative Examples 4-5. This indicates that variations in the molecular weight of chitosan affect the compressive stress and compressive modulus of the aerogel samples at 80% strain.

[0086] Further analysis of the data from Examples 1-4 and Examples 11-12 revealed that, with increasing chitosan molecular weight, the compressive stress and compressive modulus of the aerogel samples at 80% strain exhibited a trend of first increasing and then decreasing. This indicates that when the chitosan molecular weight exceeds the range specified in this application, whether too large or too small, it will affect the compressive stress and compressive modulus of the aerogel samples at 80% strain, thereby affecting the mechanical properties of the aerogel samples.

[0087] A comparison of the water contact angle and thermal conductivity data of Examples 1-4, 11-12, and Comparative Examples 4-5 reveals that the water contact angles of Examples 1-4 and 11-12 are significantly larger than those of Comparative Example 4-5, indicating that Examples 1-4 and 11-12 exhibit better hydrophobic properties than Comparative Example 4-5. Furthermore, the thermal conductivity of Examples 1-4 and 11-12 is lower than that of Comparative Example 4-5, suggesting that Examples 1-4 and 11-12 provide better thermal insulation than Comparative Example 4-5. These results indicate that variations in the molecular weight of chitosan affect the water contact angle and thermal conductivity of the aerogel samples, thereby influencing their hydrophobic properties and thermal insulation performance.

[0088] Further analysis of the data from Examples 1-4 and Examples 11-12 revealed that, with increasing chitosan molecular weight, the water contact angle of the aerogel samples initially increased and then decreased, while the thermal conductivity initially decreased and then increased. These results indicate that when the chitosan molecular weight exceeds the range specified in this application, whether too large or too small, it affects the water contact angle and thermal conductivity of the aerogel samples, thereby impacting their hydrophobic properties and thermal insulation performance.

[0089] Compared to Examples 1-4 and Examples 11-12, Comparative Example 6 showed a smaller water contact angle and a higher thermal conductivity, indicating that using a sufficient amount of chitosan with an excessively large molecular weight would affect the hydrophobic properties and thermal insulation effect of the aerogel.

[0090] In the embodiments, the volume shrinkage rate, specific surface area, porosity, compressive stress at 80% strain, compressive modulus, water contact angle, thermal conductivity, etc. of Examples 4-22 fluctuate, but the variation range is not particularly large. This result shows that when the parameters in this application are used, the aerogel obtained in the end can still have good three-dimensional network structure, mechanical properties, hydrophobic properties and thermal insulation properties.

[0091] The volume shrinkage rate, specific surface area, porosity, compressive stress at 80% strain, compressive modulus, water contact angle, and thermal conductivity of Example 3 are all at relatively high levels compared to the examples.

[0092] The difference between Comparative Example 1 and Example 3 is that the hydrophobic modification treatment in step six is ​​not used; The difference between Comparative Example 2 and Example 3 is that chitosan solution B is not used and steps related to chitosan are omitted; The difference between Comparative Example 3 and Comparative Example 1 is that the chitosan solution is further omitted; the difference between Comparative Example 3 and Example 3 is that the hydrophobic modification treatment in step six is ​​not used and chitosan solution B is not used and steps related to chitosan are omitted.

[0093] Therefore, 1. The following experimental methods were used to conduct experiments on Example 3, Comparative Example 2, and Comparative Example 3 respectively, to obtain... Figure 1 ; 2. Experiments were conducted on Example 3, Comparative Example 1, and Comparative Example 3 using experimental methods ②, ③, and ④, respectively, to obtain... Figures 2-4 .

[0094] ① The microstructure of the aerogel samples was analyzed using a scanning electron microscope (ZEISS Sigma 360, Germany); ② The chemical structure of the aerogel was analyzed using a Fourier transform infrared spectroscopy (FTIR, Thermo Fisher Scientific Nicoleti S20, USA); ③ The crystal structure of the aerogel was analyzed by X-ray diffraction (XRD, Rigaku Smart Lab SE, Japan); ④ Evaluation of the thermal insulation performance of aerogel samples: The aerogel samples were cut into cylindrical samples with a diameter of 100 mm and a thickness of 15 mm. At an ambient temperature of 25℃, the lower surface of the sample was placed on a stable heat source at a constant temperature (40℃ or 60℃). Three fixed temperature measurement points (Tp1, Tp2, Tp3) were selected on the upper surface of the sample. The temperature of the measurement points Tp1, Tp2, and Tp3 on the upper surface of the sample was measured every 2 minutes using an infrared thermometer (Hikvision HM / TPH13Pro / 3AQF / W), and the temperature rise of the measurement points from the ambient temperature of 25℃ was recorded.

[0095] For the obtained Figures 1-4 A detailed analysis will be conducted.

[0096] Figure 1The images shown are SEM images of samples from Example 3 and Comparative Examples 2 and 3. In Example 3, the particles are small and uniformly distributed with low aggregation, forming a fine, continuous porous structure with small and dense pore sizes. In Comparative Example 2, the particles show significant aggregation, forming larger "cluster-like" structures with some pores being larger and uneven in size. In Comparative Example 3, the particles exhibit even higher aggregation, a looser and more disordered structure, greater variation in pore size, and an increased proportion of large pores. Therefore, Figure 1 This demonstrates that there are significant differences between the internal three-dimensional mesh structure of Example 3 and Comparative Examples 2 and 3.

[0097] Figure 2 The FT-IR spectra of the samples from Example 3 and Comparative Examples 1 and 3 show that the infrared transmittance of the three samples is different. The infrared transmittance of Comparative Example 1, Example 3, and Comparative Example 3 increases in that order, indicating that the types or contents of functional groups of the three samples are different. Moreover, the fingerprint regions of Example 3, Comparative Example 1, and Comparative Example 3 show significant differences, indicating that the functional groups of the three samples are different. Among them, the infrared transmittance and fingerprint region absorption of Example 3 are moderate, indicating that the content of chemical functional groups in Example 3 is moderate, and the molecular skeleton and functional connection mode are different from those of Comparative Examples 1 and 3.

[0098] Figure 3 The XRD patterns of the samples from Example 3 and Comparative Examples 1 and 3 are shown. Example 3 exhibits a clear main peak and moderate crystallinity, while Comparative Example 1 shows broadened diffraction peaks with low intensity. This may be because the amorphous structure has weak intermolecular forces, leading to disordered heat conduction paths but enhanced solid thermal conductivity, resulting in poor thermal insulation. Comparative Example 3 shows sharp and high-intensity diffraction peaks, likely due to strong intermolecular forces in its highly crystalline structure and orderly molecular arrangement within the crystal, potentially forming continuous heat conduction paths, thus resulting in poor thermal insulation performance.

[0099] Figure 4 At temperatures of 40°C and 60°C, the upper surface temperature of Example 3 is lower than that of Comparative Example 1.

[0100] In summary, this demonstrates that Example 3 has a better heat insulation effect.

[0101] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing a hydrophobic chitosan grafted silica aerogel, characterized in that, The method comprises the following steps: Step one, fully mix tetraethyl orthosilicate, deionized water and N, N- dimethylformamide at room temperature to obtain a silicon solution A; Fully mix glacial acetic acid, deionized water and chitosan at a temperature of 50-55℃ to obtain a chitosan solution B; Step two, fully mix the silicon solution A and the chitosan solution B to obtain a mixed solution C; Step three, add acetic acid solution to the mixed solution C to adjust the pH to 2-4, and then hydrolyze at a temperature of 40-50℃ for 75-120 min to obtain a sol D; Step four, add ammonia water to the sol D to adjust the pH to 7-8, and then perform polycondensation reaction for 20-60 min to obtain a gel E; Step five, place the gel E in anhydrous ethanol for aging treatment to obtain a chitosan grafted silica wet gel F; Step six, modify the chitosan grafted silica wet gel F in a hydrophobic modification liquid prepared by mixing a hydrocarbyl chlorosilane and n-hexane, and then clean the chitosan grafted silica wet gel G with n-hexane after taking out to obtain a hydrophobic chitosan grafted silica wet gel G; Step seven, freeze dry the hydrophobic chitosan grafted silica wet gel G to obtain a hydrophobic chitosan grafted silica aerogel. The chitosan in the step one has a molecular weight of 1-100,000 Da. The mass ratio of the chitosan to the tetraethyl orthosilicate in the mixed solution C in the step three is 1: (90-110).

2. The method of claim 1, wherein the hydrophobic chitosan grafted silica aerogel is prepared by the steps of: The mass ratio of the chitosan to the tetraethyl orthosilicate in the mixed solution C in the step three is 1: (95-105).

3. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, In the step one, the mass ratio of the tetraethyl orthosilicate, the deionized water and the dimethylformamide is 1: (2-3) : (0.25-0.45).

4. The method of claim 1, wherein the hydrophobic chitosan grafted silica aerogel is prepared by the steps of: In the step one, the mass ratio of the glacial acetic acid, the deionized water and the chitosan is 1: (35-55) : (0.8-1.2).

5. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, The chitosan in the step one has a molecular weight of 4-70,000 Da.

6. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, In the step five, the mass to volume ratio of the wet gel E to the anhydrous ethanol in the aging treatment is 1: (50-100) g / ml, the aging treatment temperature is 45-70℃, and the treatment time is 9-15 h.

7. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, In the step six, the volume ratio of the hydrocarbyl chlorosilane to the n-hexane is 1: (8-12), the mass to volume ratio of the wet gel E to the hydrophobic modification liquid in the modification treatment is 1: (15-30) g / ml, and the modification treatment time is 10-15 h. The hydrocarbyl chlorosilane is one or more mixtures of trimethylchlorosilane, dichlorodimethylsilane, monomethyltrichlorosilane, triethylchlorosilane, ethyltrichlorosilane, propyltrichlorosilane, tert-butyltrichlorosilane, tert-butyldimethylchlorosilane, isobutyltrichlorosilane, hexyltrichlorosilane, cyclohexyltrichlorosilane, n-octyltrichlorosilane, phenyldimethylchlorosilane, and further preferably one or more mixtures of trimethylchlorosilane, triethylchlorosilane and phenyldimethylchlorosilane.

8. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, The freeze-drying in the step seven comprises pre-freezing treatment and low-temperature drying treatment; the pre-freezing treatment time is 6-12 h, and the pre-freezing treatment temperature is-15℃ to-30℃; the low-temperature drying treatment time is 12-36 h, and the low-temperature drying treatment temperature is-50℃ to-80℃.

9. The method for preparing a hydrophobic chitosan-grafted silica aerogel according to claim 1, characterized in that, The molar concentration of the acetic acid solution in the step three is 1 mol / L; and the molar concentration of the ammonia water in the step four is 5 mol / L.

10. A hydrophobized chitosan grafted silica aerogel, characterized in that, The hydrophobic chitosan grafted silica aerogel is prepared by the method in any one of claims 1-9.

Citation Information

Cited By

  • Heat-conducting and hydrophobically-modified phosphorus-nitrogen halogen-free flame retardant chitosan aerogel as well as preparation method and application of heat-conducting and hydrophobically-modified phosphorus-nitrogen halogen-free flame retardant chitosan aerogel

    CN121949878A